The evolving role of TERT alterations in meningioma risk stratification - Maas, Sybren L. N.; Perry, Arie; Sahm, Felix (Neuro-Oncology, 2025)
Similar to other central nervous system (CNS) tumors, the 2021 fifth edition of the World Health Organization (WHO) classification system (CNS5) introduced molecular markers as independent meningioma grading criteria for the first time.1 Specifically, the presence of homozygous CDKN2A/B deletion and/or telomerase reverse transcriptase gene promoter (TERTp) mutation warrants a CNS WHO grade 3 designation regardless of histologic features. As homozygous loss of CDKN2A/B disables both RB- and p53-mediated cell cycle control, and TERTp mutation overcomes senescence by maintaining telomere length, a more aggressive tumor biology makes sense conceptually. Multiple independent publications now confirm both as enriched in morphologically high-grade cases, with reduced progression-free or overall survival times.2-6 Two back-to-back publications in Lancet Oncology now re-explore the role of TERT in meningioma prognosis and grading.7,8
Vorab veröffentlicht: 10. Oktober 2025
Gesehen am 18.02.2026